The knowledge organisation of sub-subgenres: the curious case of the collaborative works of Gilbert and Sullivan - Deborah Lee (Information Research: An International Electronic Journal)
Introduction. This paper explores the knowledge organisation of sub-subgenres and takes a micro-level approach to genre classification. The study uses a particular case study: the classification issues around the collaborative works of Gilbert and Sullivan.